Exploration of collaborative learning environments in New Zealand secondary school science - Taylor, Simon P. G. (Curtin University, 2012)
This thesis is based on a project named Please Let Us Take Off (PLUTO) which recognized the need to further consider students’ attitudes and perceptions of their science experiences at secondary school and to examine their immediate learning environment. Nuthall (2005) spent many years in New Zealand classrooms monitoring and analysing student interactions using microphones that recorded student conversations. His major conclusion related to how little teachers knew about what was going on in classrooms. Nuthall claimed the world of learning from a student’s perspective and the specific evidence of what is happening in the student personal learning space can be unknown to the teacher. Most importantly, the project wanted to encourage teachers to take the opportunity to look closer into the student’s personal viewpoint of learning in science lessons.In the year 2008, New Zealand was introducing a new national curriculum and there was also considerable concern for non-engaged students and for Māori students in their early years of secondary school. There was appreciation of the new curriculum and its principles by schools but still an overwhelming necessity to gain further and deeper understanding of the actual learners’ science experiences. Hence the attention of this study, to gain further knowledge of how students view their science learning, initially by the use of the Constructivist Learning Environment Survey (CLES). A range of qualitative student voice, including learning drawings made by students, were collected and analyzed to gain additional insight into the experiences of secondary science students.This thesis focuses on students entering secondary school and their learning experiences in science in their first two years at years 9 and 10. It was action-research based and it followed 15 classes of students at years 9-10 (13-15 years old) with their corresponding teachers in 12 secondary schools, over three consecutive years, 2009-2011.The selected geographical region of research incorporated a range of rural and urban secondary schools in the central North island of New Zealand. The study measured students’ attitudes and perceptions of their experiences of the classroom and it intended to generate an opportunity for teachers to discuss and reflect on the research data gathered.The students were surveyed using the Constructivist Learning Environment Survey over two years. The data were analysed using SPSS and comparisons were made between actual and preferred learning environment results. Variations between each year, gender differences and ethnicity differences were also measured and evaluated. Student learning drawings were adopted in the year 2011 to gather qualitative voice and the drawings were analysed by considering the choices that the students made in their drawing. The student audio interviews also added a wealth of student voice to further explore the students’ perceptions of their learning in science lessons. The five scales used in the CLES survey were used in the analysis of the student learning drawings and the nature of the interview questions posed to the students.The PLUTO project endeavoured to support teacher professional learning and act as a catalyst to encourage ongoing professional discourse. It offered the opportunity to make measurements of the learning environment and at the same time help provide reasons to use different teaching methods in the science classes that may have not been used before.